2011
DOI: 10.1093/bja/aeq341
|View full text |Cite
|
Sign up to set email alerts
|

Continuous S -(+)-ketamine administration during elective coronary artery bypass graft surgery attenuates pro-inflammatory cytokine response during and after cardiopulmonary bypass

Abstract: Our data demonstrate that S-(+)-ketamine possesses anti-inflammatory potential. Anaesthesia with S-(+)-ketamine may have beneficial effects in attenuating the CPB-induced systemic inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 40 publications
(33 reference statements)
5
41
1
2
Order By: Relevance
“…One possibility might be an anti-inflammatory effect of S-ketamine [28], but our measurements of the inflammatory parameters in plasma and BALF do not support this notion. It also appeared possible that the 6 hours' exposure rendered the alveolar epithelium insensitive to S-ketamine.…”
Section: Discussioncontrasting
confidence: 59%
“…One possibility might be an anti-inflammatory effect of S-ketamine [28], but our measurements of the inflammatory parameters in plasma and BALF do not support this notion. It also appeared possible that the 6 hours' exposure rendered the alveolar epithelium insensitive to S-ketamine.…”
Section: Discussioncontrasting
confidence: 59%
“…It also facilitated rehabilitation at 1 month and decreased postoperative chronic pain up to 6 months after surgery [101] . One study demonstrated that S(+)-ketamine (1-3 mg/kg bolus, followed by 2-4 mg•kg -1 •h -1 ) during elective coronary artery bypass graft surgery exerts anti-inflammatory effects during and after cardiopulmonary bypass [102] . Although these studies were based on inflammatory markers, large prospective human studies are warranted for clinical outcomes.…”
Section: Anti-inflammationmentioning
confidence: 99%
“…[79][80][81] The use of ketamine in cardiac surgery was associated with decreased inflammation, opioid sparing, and improved patient satisfaction postoperatively. [82][83][84][85][86][87][88][89][90] Its use in the prevention of chronic poststernotomy pain has not been studied.…”
Section: Acetaminophenmentioning
confidence: 99%